Didyma, Türkei: Restaurierung und Konsolidierung des Apollontempels - Bumke, Helga; Kronewirth, Christoph (e-Forschungsberichte des DAI, 2023)
The former architect and Bauforscher Hubert Knackfuß, responsible for excavation and reconstruction of the temple of Apollo at Didyma between 1907 and 1913, established certain and for his time remarkably progressive standards for restoration, which are partly still applied today, as e.g. the preservation of the original building material. Based on his work and guided by the expertise of a qualified commission, restoration work has again been carried out annually since 1992 until today.